TRANSLATION STRATEGIES OF INFORMAL ENGLISH EXPRESSIONS ON SOCIAL MEDIA X: Strategi Penerjemahan Ekspresi Bahasa Inggris Informal di Media Sosial X - Candradiva, Fernolivia; Fatimah, Rezki (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the translation strategies applied to informal English expressions, slang, abbreviations, and memes found on the social media platform X (formerly Twitter), focusing on how these context-dependent expressions are translated into Indonesian. The rise of informal language on digital platforms presents challenges for translators due to its dynamic, highly creative, and non-standardized nature. This study aims to identify and categorize the types of informal English expressions and analyze the translation strategies used using Peter Newmark’s frameworks while preserving the meanings and relevances. Using a descriptive qualitative method, the data consists of 21 posts from 3 accounts on X, selected purposively to represent various informal expressions. Each post was translated using DeepL and retranslated manually by the researcher, then analyzed to determine the dominant translation method and translation procedures applied. The findings show that Idiomatic Translation was the most dominant method, while the most frequently used procedures were Modulation, Descriptive Equivalent, and Transference. This study proposes new insights into translating informal digital discourse, especially for slang, abbreviations, and memes on social media, emphasizing that context-sensitive and real-time evolving language used in everyday online interaction is essential for professional translation practice.